2009
DOI: 10.1142/s0192415x09007302
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Comparative Effects of Hawthorn Fruit Compound and Simvastatin on Lowering Blood Lipid Levels

Abstract: This project studied the lowering blood lipids effect in atherosclerotic ApoE-deficient mice. Group A mice (n = 6), fed with a normal diet, served as the negative control. The experimental groups used mice fed with a high cholesterol diet (HCD) for eight weeks, and then selected for inclusion in the study on the basis of high blood lipid levels and the formation of atherosclerotic lesion plaque, which was indicated by an ultrasound biomicroscopy test. Eighteen mice met the selection criteria (atherosclerotic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 7 publications
2
14
0
1
Order By: Relevance
“…However, it significantly decreased plasma and hepatic TG levels, although it is one of the most frequently used cholesterol-lowering agents. A study by Xu et al 41 suggested that simvastatin supplementation with a high cholesterol diet significantly lowered plasma TG, but not the LDL-C. Steinmetz et al 42 also suggested that treatment with simvastatin had no effect on the serum cholesterol levels in either normal or hypercholesterolemic mice.…”
Section: Figmentioning
confidence: 99%
“…However, it significantly decreased plasma and hepatic TG levels, although it is one of the most frequently used cholesterol-lowering agents. A study by Xu et al 41 suggested that simvastatin supplementation with a high cholesterol diet significantly lowered plasma TG, but not the LDL-C. Steinmetz et al 42 also suggested that treatment with simvastatin had no effect on the serum cholesterol levels in either normal or hypercholesterolemic mice.…”
Section: Figmentioning
confidence: 99%
“…Similar study showed that Hawthorn fruit compound lowered blood lipids in atherogenic diet fed, ApoE gene deficient atherosclerotic mice. The results showed that Hawthorn fruit compound significantly reduced the ratio between low-density lipoprotein cholesterol (LDL-C) and serum cholesterol (TC): (LDL-C)/TC, especially the triglyceride (TG) levels [76]. Besides, TCR can significantly increase the binding of 125 I-LDL to the liver plasma membranes in vitro.…”
Section: Cardiovascular Effectmentioning
confidence: 99%
“…Nevertheless, drugs are not effective on all patients and have side effects that may aggravate the patients’ symptoms and signs. Some fruits (extract) possess similar or even more potent anti-hypertensive, lipid-lowering, and hypoglycemic activities, which has inspired many researchers to explore new therapies for CVDs [9,10,11,12]. The cardioprotective mechanisms of fruits are not entirely clear, but their outstanding antioxidant and free radical scavenging properties are considered principal [13].…”
Section: Introductionmentioning
confidence: 99%